Knowledge spillovers to industry: Opportunities for universities of applied sciences - Bernd Ebersberger; Sverre Herstad; Andreas Altmann (Forum Neue Medien in der Lehre Austria, 2012)
The paper condenses recent empirical findings about the characteristics of those firms that utilize and appreciate knowledge spillovers from higher education organizations. We discuss these findings, sketch out how these empirical findings relate to the third mission of universities and how this can present opportunities for universities of applied sciences. 30.03.2012 | Bernd Ebersberger (Innsbruck), Sverre J. Herstad (Oslo) & Andreas Altmann (Innsbruck)